2002
DOI: 10.1080/0028825x.2002.9512789
|View full text |Cite
|
Sign up to set email alerts
|

New records of snow algae for New Zealand, from Mt Philistine, Arthur's Pass National Park

Abstract: Eight out of nine species of snow algae occurring on Mt Philistine, Arthur's Pass National Park, are new records for New Zealand. Chlainomonas kolii, reported previously in snow beneath tree canopies in the USA, is responsible for blooms which colour the snow red. Chloromonas rubroleosa, which is found in red snow dominated by C. kolii, also occurs in continental Antarctica. Three other species of Chloromonas, including the relatively common bipolar alga previously known as Scotiella antarctica, occur in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…K. inundata also has the laminate chloroplast and tapered end cells in common with those occurring in the few-celled filaments of Raphidonema and in unicells or twin-celled filaments of Koliella (these two genera are often considered to be congeneric (Skuja 1969;Hoham 1973;Wehr & Sheath 2003)). In a recent paper on snow algae of New Zealand, Novis (2002) reported the rare presence of bilobed chloroplasts in easily fragmenting few-celled filaments of Raphidonema nivale in association with the occurrence of one or two chloroplasts per cell. It is emphasized here that the indeterminate growth of K. inundata filaments and the strictly bilobed character of the single chloroplast in its vegetative cells makes Koliellopsis a distinct genus.…”
Section: Discussionmentioning
confidence: 99%
“…K. inundata also has the laminate chloroplast and tapered end cells in common with those occurring in the few-celled filaments of Raphidonema and in unicells or twin-celled filaments of Koliella (these two genera are often considered to be congeneric (Skuja 1969;Hoham 1973;Wehr & Sheath 2003)). In a recent paper on snow algae of New Zealand, Novis (2002) reported the rare presence of bilobed chloroplasts in easily fragmenting few-celled filaments of Raphidonema nivale in association with the occurrence of one or two chloroplasts per cell. It is emphasized here that the indeterminate growth of K. inundata filaments and the strictly bilobed character of the single chloroplast in its vegetative cells makes Koliellopsis a distinct genus.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it would not be surprising if several of the taxa recorded here could be isolated from other environments in New Zealand; indeed, this does seem to be the case with Klebsormidium dissectum (Novis 2006 The limited alpine algal taxa known to date suggest communities of organisms with widely differing habitat range. for example, despite being regarded as an opportunistic soil taxon that colonises snow, Stichococcus was not isolated from any other habitat in this study, and the obligate species found in snow previously from the site (Novis 2002b) never appeared in samples from soil or pools. This contrasts with the distributions of Klebsormidium and Chrysocapsa as discussed above.…”
Section: An Alpine Flora?mentioning
confidence: 95%
“…Morphologically identical strains of Chrysocapsa have appeared in New Zealand and Australia; no other chrysophyceans grew in our New Zealand cultures and it seems most unlikely that entire swarms of other chrysophycean species have been selected out by our culture conditions (another chrysophycean, Chromulina sp., was cultured from the site previously (Novis 2002b), but field analysis over two seasons showed that it was not always present (Novis 2002a)). however, it is possible that some more strains would have grown with more variation in culture conditions.…”
Section: Problem Of Falsificationmentioning
confidence: 99%
“…During the 20th century, systematic studies on these algae have been undertaken to identify the different species growing on or in the snow and to describe the species causing not only 'red snow' but also green, yellow, orange, or even grey snow (a comprehensive summary of the current state of knowledge of systematics, occurrence and physiology of snow algae is given by Hoham & Duval, 2001). The organisms causing these various snow colourations proved to be mostly green algae, but the exact taxonomic identity is often unclear and further investigation using electron microscopy and molecular methods is required (Mu¨ller et al, 1998;Hoham et al, 2002;Novis, 2002).…”
Section: Introductionmentioning
confidence: 99%